Foreign direct investment, institutional quality and business regulatory environment: Evidence from Africa - Abdelghany, Nada (AUC Knowledge Fountain, 2020)
Foreign direct investment (FDI) plays a significant role in both the economic growth and development of a nation. Given Africa's development and economic characteristics, FDI is an attractive tool for economic development. Hence, understanding the key drivers of FDI is of major importance to help promote the sustainable development of the private sector. This thesis focuses on the interrelation between two key determinants of FDI inflows: institutional quality and the business regulatory environment, while controlling for economic determinants including the market and resource characteristics of a country. Using a panel of 46 countries for the period 2012-2016, a mediation analysis is employed to examine the relationship between an established governance index, as a proxy measure of institutional quality, using Worldwide Governance Indicators (WGI) and the doing business score developed by the World Bank (WB), as a proxy measure of business regulatory environment. The conditions of mediation analysis were tested using a number of multivariate log-linear regression models. The model is estimated using fixed effect panel regression analysis with robust cluster standard error to account for homoscedasticity and serial autocorrelation. The data on the included variables were gathered from publicly available resources. In line with literature such as Globerman and Sharpio (2002) and Gani (2007), the findings of the study regarding the relevance of governance index for FDI inflows showed a robust, consistent significance using different estimation techniques. However, contrary to the literature such as Piwonski (2010) and Morriz and Aziz (2011), the business regulatory environment did not demonstrate any robust significance to FDI inflows. Though these findings result in a statistical rejection of the main hypothesis, it does not constitute conclusive evidence that the business regulatory environment does not mediate the effect of institutional quality on FDI inflows within the African context. This is due to a concern regarding the validity of the doing business score validity as a proxy for the business regulatory environment.